2009
DOI: 10.1111/j.1863-2378.2008.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Mycobacterium bovis in Bovine Lymph Nodes by PCR

Abstract: Thirty-five lymph node samples were taken from animals with macroscopic lesions consistent with Mycobacterium bovis infection. The animals were identified by postmortem examination in an abattoir in the northwestern region of state of Paraná, Brazil. Twenty-two of the animals had previously been found to be tuberculin skin test positive. Tissue samples were decontaminated by Petroff's method and processed for acid-fast bacilli staining, culture in Stonebrink and Lowenstein-Jensen media and DNA extraction. Lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 22 publications
1
36
0
5
Order By: Relevance
“…We observed a good agreement between culture and PCR (Ä = 0.61), implicating that a high number of samples yielded a positive result by both tests, and confirming that culture and PCR are the most important diagnostic tools for the diagnosis of BTB in dairy areas (Cardoso et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We observed a good agreement between culture and PCR (Ä = 0.61), implicating that a high number of samples yielded a positive result by both tests, and confirming that culture and PCR are the most important diagnostic tools for the diagnosis of BTB in dairy areas (Cardoso et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…The Se of nucleic acid amplification can be influenced by different factors, such as insufficient quantity of bacilli or the presence of inhibitors hampering the polymerase (Mangiapan et al, 1996;Pires de Araújo et al, 2005;Cardoso et al, 2009). In Brazil, comparison between different concentrations and volumes of DNA samples showed that the percentage of PCR-positive lymph nodes increased from 39.4% to 54.5% after re-analysis of the initially negative samples using a 1:2 dilution of the suspension and 2,5 l instead of 1 l (Cardoso et al, 2009). In our study, we used 10 l of undiluted DNA extract for the PCR, implicating that the sensitivity of our PCR might increase by the use of diluted DNA extracts, thus minimizing the effect of possible inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Um animal que apresentava BAAR foi negativo aos testes moleculares. Sabe-se que a sensibilidade das técnicas de PCR pode ser afetada pela presença de inibidores e pela quantidade de DNA na amostra clínica (Cardoso et al 2009), porém, neste estudo, a presença de inibidores foi testada.…”
Section: Discussionunclassified
“…Diversos estudos vêm demonstrando a possibilidade do uso da PCR no diagnóstico da tuberculose bovina, permitindo uma maior acurácia e significativa redução do tempo do diagnóstico em relação aos métodos tradicionais de identificação dos isolados (Zanini et al 2001, Cardoso et al 2009, Collins 2011. Estudos epidemiológicos moleculares da tuberculose bovina têm sido utilizados para monitoramento e controle do comércio de animais, bem como para a investigação da origem da infecção (Figueiredo et al 2011).…”
Section: Introductionunclassified